REGIONAL JUSTICE AND NATIONAL UNITY - V. P. Loguinov (Модернизация, инновация, развитие, 2016)
In regions of Russia who lag behind the national average both in pay and in economic development, the problem of raising living standards should be solved through a nation-wide program which would be believed by peoples of Russia regardless of ethnicity. It should include creation of jobs, leveling of wages, abolition of fees for education and for a significant portion of health services, reducing utility tariffs and prices for public transportation, introduction of an income-based progressive taxation system, improving law enforcement activities, etc. Considerable attention is paid to the analysis of macroeconomic indicators of Russian economy in recent years.